2011
DOI: 10.1186/1475-2859-10-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis reveals Lactobacillus sanfranciscensis as stable element in traditional sourdoughs

Abstract: Sourdough has played a significant role in human nutrition and culture for thousands of years and is still of eminent importance for human diet and the bakery industry. Lactobacillus sanfranciscensis is the predominant key bacterium in traditionally fermented sourdoughs.The genome of L. sanfranciscensis TMW 1.1304 isolated from an industrial sourdough fermentation was sequenced with a combined Sanger/454-pyrosequencing approach followed by gap closing by walking on fosmids. The sequencing data revealed a circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 60 publications
0
79
1
4
Order By: Relevance
“…However, the low number of transposases in these strains of W. cibaria is in stark contrast to the 111 found in another sourdough LAB, Lactobacillus sanfranciscensis TMW 1.1304, in which it was suggested that their high number facilitated niche adaptation of this strain (Vogel et al, 2011).…”
Section: Genomics Of Weissellacontrasting
confidence: 63%
See 2 more Smart Citations
“…However, the low number of transposases in these strains of W. cibaria is in stark contrast to the 111 found in another sourdough LAB, Lactobacillus sanfranciscensis TMW 1.1304, in which it was suggested that their high number facilitated niche adaptation of this strain (Vogel et al, 2011).…”
Section: Genomics Of Weissellacontrasting
confidence: 63%
“…Oxygen tolerance. Tolerance of oxygen in LAB generally requires the presence of NADH oxidase or several thiol-active enzyme systems, including the glutathioneglutathione reductase system, the thioredoxin-thioredoxin reductase couple and cysteine uptake and metabolism capability (Vogel et al, 2011). In the genome of W. cibaria MG1 putative homologues of functional proteins in these systems were identified, including an NADH oxidase, three glutathione reductase genes, a glutathione peroxidase and thioredoxin reductase.…”
Section: Genomics Of Weissellamentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, genome assembly was done using different versions of Newbler assembler 33,39 except in a few cases where gsAssembler 36,37 or CLC Genomics Workbench 37 Phred-Phrap-Consed software package 41 . Genome annotation was done using the Rapid Assembly using Subsystems Technology (RAST) server 38 -40 , often combined with Glimmer 38 , tRNAscan-SE 38 , RNAmmer 38 , EDGAR 36 , PEDANT 41 , GeneMark 41 , and NCBI Prokaryotic Genome Automated Annotation Pipeline (PGAAP) analysis 33,36 .…”
Section: Genomic Technologies In Probiotic Researchmentioning
confidence: 99%
“…Genome annotation was done using the Rapid Assembly using Subsystems Technology (RAST) server 38 -40 , often combined with Glimmer 38 , tRNAscan-SE 38 , RNAmmer 38 , EDGAR 36 , PEDANT 41 , GeneMark 41 , and NCBI Prokaryotic Genome Automated Annotation Pipeline (PGAAP) analysis 33,36 .…”
Section: Genomic Technologies In Probiotic Researchmentioning
confidence: 99%